Calcimimetics and Vascular Calcification - Avinash Chandu; Carolt Arana; Juan Daniel Díaz-García; Mario Cozzolino; Paola Ciceri; José-Vicente Torregrosa (Toxins)
In patients with chronic kidney disease (CKD), cardiovascular events (CVA) are the main cause of morbidity and mortality. Vascular calcification, linked to bone mineral metabolism disorders such as elevated serum phosphate, parathyroid hormone (PTH), and FGF23, well-known uremic toxins, aggravate this risk. Calcimimetics are allosteric activators of the calcium-sensing receptor (CaSR), a G protein-coupled receptor that regulates PTH secretion and synthesis in response to changes in extracellular calcium in the parathyroid glands. Through direct and indirect mechanisms, they have demonstrated their efficacy in reducing the progression of vascular, valvular, and soft tissue calcification in experimental studies. Although clinical studies in dialysis patients did not achieve statistical significance in their primary objectives, positive results in subgroup analyses suggest that the lack of significance may be attributable to the short follow-up period. This finding highlights the need to consider early treatment strategies, especially in advanced stages of chronic kidney disease, to more effectively address the progression of vascular calcification through serum uremic toxins control.